2021
DOI: 10.1002/ajcp.12558
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving fairness in an unfair world: System justification and the mental health of girls in detention facilities

Abstract: Psychologists in the helping professions have long accepted the idea that cognitions have implications for mental health and wellbeing. Community psychologists have further established the importance of context and systems in the etiology of mental health problems. In this paper, we argue that as a discipline that prioritizes social justice, community psychology should consider associations between cognitions about structural and systemic inequality and individual mental health, particularly in marginalized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…This has also been reported in a study from Indian prisons which found that women were provided more services compared to men in terms of parenting and counselling classes, support groups and day care services, contributing to significantly reduced mental health challenges (Mishra et al , 2021). In contrast, a study on the mental health of youth detainees in the USA found that male juveniles experienced more fairness in care than their female counterparts, which was found to have significant positive effects on their internalising and externalising problems (Sichel et al , 2022). This differential perception of prison settings among men and women may indicate gender issues in different contexts and cultures within the prison system of care and available privileges in high- and low-income countries that need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been reported in a study from Indian prisons which found that women were provided more services compared to men in terms of parenting and counselling classes, support groups and day care services, contributing to significantly reduced mental health challenges (Mishra et al , 2021). In contrast, a study on the mental health of youth detainees in the USA found that male juveniles experienced more fairness in care than their female counterparts, which was found to have significant positive effects on their internalising and externalising problems (Sichel et al , 2022). This differential perception of prison settings among men and women may indicate gender issues in different contexts and cultures within the prison system of care and available privileges in high- and low-income countries that need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Drawing upon the existing studies on Internet use (Ma & Zhu, 2020 ; Vatsa et al, 2022 ; Zhang et al, 2019 ; Zheng et al, 2021 ) and negative affect (Akpınar, 2021 ; Chekroud et al, 2018 ; Lee et al, 2021 ; Sichel et al, 2022 ; Zhang et al, 2022 ), we selected a number of control variables to capture individual, household and contextual characteristics. They include respondents’ age, gender, education, working status, exercise, lunch break habit, reading experience, family size, elder ratio, child ratio, and living location.…”
Section: Data Variables and Descriptive Statisticsmentioning
confidence: 99%